2022
DOI: 10.36740/wlek202208201
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis in Patients in Post-Covid-19 Period: Etiology, Clinical and Morphological Characteristics

Abstract: The aim is to identify the etiology, clinical and morphological features of rhinosinusitis in patients in post-COVID-19 period. Materials and methods: In the present study, it was carried out the analysis of 11 cases of rhinosinusitis, which developed after COVID-19 infection. The diagnosis of rhi¬nosinusitis was established on the basis of anamnesis, clinical and laboratory examination, specialized instrumental examination (rhinoendoscopy, X-ray, magnetic resonance imaging, spiral and 3D computed tomography)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
3
0
0
Order By: Relevance
“…Our current study showed that 84.9% of the patients were bilateral and 15.1% of the patients were unilateral. This agree with Myroshnychenko et al [7] who reported that in 9 cases [81.8%] rhinosinusitis was bilateral and in 2 cases [18.2%] were unilateral.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our current study showed that 84.9% of the patients were bilateral and 15.1% of the patients were unilateral. This agree with Myroshnychenko et al [7] who reported that in 9 cases [81.8%] rhinosinusitis was bilateral and in 2 cases [18.2%] were unilateral.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the mean duration which rhinosinusitis developed after COVID-19 infection was 43.17 ± 7.23 days with range 34 -60 days. These results agree with Myroshnychenko et al [7] who reported that the mean number of days during which rhinosinusitis developed after COVID-19 infection was 41.2±4.63 days However, our results disagree with El-Kholy et al [11] who reported that in patients with CRS, the mean duration for development of CRS after COVID-19 was 17.82±2.97 days.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation